2022
DOI: 10.1021/acsanm.1c03273
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring Electrode Surfaces and Hydrogels for Enhanced Thermocapacitance

Abstract: Thermogalvanic cells have the ability to convert low-temperature waste heat energy (<200 °C) into electrical energy. However, these systems cannot store this electrical energy. Thermocapacitors use analogous mechanisms to convert heat into electrical energy, but crucially can store this electrical energy. Previous work has used polyelectrolyte gels to frustrate the mobility of a redox couple, causing an accumulation of charge imbalance at the two electode:gelled electrolyte interfaces, resulting in stored ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Gelled or 'quasi-solid' electrolytes have appeared numerous times, e.g. 9,10,[12][13][14][44][45][46][47][48] in thermogalvanic cells as a method of producing an electrolyte which is not susceptible to leaking and so supported the development of wearable devices; 9,10 theoretically it also reduces the thermal conductivity through the thermocell. We therefore investigated the effect of gelling the electrolyte, especially since gelation was expected to 'switch off' the convection found to be so inuential earlier in this study.…”
Section: Effect Of Gelling the Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…Gelled or 'quasi-solid' electrolytes have appeared numerous times, e.g. 9,10,[12][13][14][44][45][46][47][48] in thermogalvanic cells as a method of producing an electrolyte which is not susceptible to leaking and so supported the development of wearable devices; 9,10 theoretically it also reduces the thermal conductivity through the thermocell. We therefore investigated the effect of gelling the electrolyte, especially since gelation was expected to 'switch off' the convection found to be so inuential earlier in this study.…”
Section: Effect Of Gelling the Electrolytementioning
confidence: 99%
“…Thermogalvanic electricity production is an entropically-driven process, and the magnitude of the driving force is normally expressed as the ‘thermogalvanic Seebeck coefficient’, or S e ;where Δ S rc is the difference in entropy between the two redox states, n is the number of electrons transferred and F is the Faraday constant. 11 The S e therefore represents the possible potential difference; Soret effects 12 and thermocapacitive effects 13,14 can also be significant contributors to the potential difference, but are only significant in fairly unique (typically gelled) systems. The S e is sensitive to the absolute concentration of the redox couple, the ratio of the concentration of the two oxidation states, and the ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…During the redox reaction process, carbon materials also offer ample ion transport channels and reaction sites, ensuring the continuity of the redox reactions. Materials such as carbon paper [29], carbon nanotubes [24,59,84,85], graphite [72,[86][87][88], and carbon cloth [60,84] have thus been widely employed in fabricating TEC electrodes. Among them, carbon textiles or carbon cloth are good candidates for flexible electrodes Buckingham et al [71] reported a P max /(∆T) 2 of 0.2375 mW K −2 m −2 and a η r of 0.131% by using carbon cloth electrodes.…”
Section: Electrodementioning
confidence: 99%
“…In recent years, significant progress has been made in liquid thermogalvanics by improving electrodes, electrolytes, and redox species [ 30 , 31 , 32 , 33 , 34 ]. In particular, studies on quasi-solid thermogalvanics have eliminated the leakage risk of liquid electrolytes by introducing physically crosslinked networks [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some flexible devices based on thermogalvanic hydrogels have been developed for human thermal energy generation, body temperature monitoring, and solar energy harvesting [ 16 , 35 , 36 ]. Inexpensive and environmentally friendly electrode and electrolyte materials form simple device structures, as well as excellent thermoelectric power performance [ 30 , 31 , 32 ]. As shown in Figure 1 , the number of publications and citations using hydrogels to harvest and sense thermal energy has increased from 2000 to 2022 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ,…”
Section: Introductionmentioning
confidence: 99%